Pengaruh Word Of Mouth, Image dan Hedonic Shopping Motivation Terhaap Keputusan Pembelian Sepatu Vans ( Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Endang Rahmawati; Siti Asiyah; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This research aimed to determine the influence of word of mouth, brand image, and hedonic shopping motivation on the decision to buy vans shoes in FEB students, Universitas Islam malang. The population was all students of the Faculty of Economics, Universitas Islam malang with a total sample of 75 respondents. The data collection technique was purposive sampling. The source of data in the research was to use primary data, and the data collection method used was a questionnaire. The results were simultaneously word of mouth, brand image, and hedonic shopping, motivation affects the interest in purchasing decisions of vans shoes. Keywords: Influence Of Word Of Mouth, Brand Image, And Hedonic Shopping.